Covalent polymer functionalization of graphene for improved dielectric properties and thermal stability of epoxy composites. (18th January 2016) - Wan, Yan-Jun; Yang, Wen-Hu; Yu, Shu-Hui; Sun, Rong; Wong, Ching-Ping; Liao, Wei-Hsin
Abstract: Incorporation of conductive fillers into polymeric matrix to fabricate the composites with light-weight and excellent dielectric performance has been considered as one of the most promising processes. However, the inevitable high dielectric loss of the composites is still an obstacle for their practical applications, which has become a challenge for a long time, and the solution for this issue is still an open question. In this study, diglycidyl ether of bisphenol-A (DGEBA) molecules were used and grafted onto reduced graphene oxide (RGO) to synthesize DGEBA functionalized RGO (DGEBA-RGO). Various characterizations including TEM, FTIR, UV–visual spectrum, TGA, Raman spectrum and XRD revealed that the DGEBA molecules were grafted onto RGO sheets successfully. The DGEBA-RGO sheets were found to significantly improve the dielectric properties and thermal stability of epoxy compared to the corresponding graphene oxide (GO) and untreated RGO sheets. For instance, at 1 kHz, epoxy composites filled with 1.00 wt% DGEBA-RGO sheets showed a dielectric constant of ∼32 at room temperature, which is over 9 times higher than that of neat epoxy (∼3.5); meanwhile, the dielectric loss of the composites was suppressed and only 0.08. The enhanced dielectric properties can be well interpreted by the duplex interfacial polarization and the micro-capacitor model. The above outstanding properties should be ascribed to the well dispersion of DGEBA-RGO and the strong interaction between the filler and polymer matrix, which are induced by effective package of grafted DGEBA molecules on the graphene surface.